Anodal stimulation of inhibitory control and craving in satiated restrained eaters. (4th May 2023) - Schroeder, Philipp A.; Farshad, Maryam; Svaldi, Jennifer
ABSTRACT : Objectives: Eating and weight disorders are severe and complex clinical conditions which, among other behaviors, include (attempts at) restrained eating, food avoidance, following dietary rules, and overeating. Comparable to women with obesity, restrained eaters (RE) without formal eating disorder diagnosis are worse at inhibiting their motor responses than unrestrained eaters (URE). According to neuroimaging studies, the right inferior frontal gyrus (rIFG) is involved in inhibitory control which, in turn, could be improved by neuromodulation such as anodal transcranial direct current stimulation (tDCS) across rIFG. Methods: This double-blind sham-controlled cross-over study was conducted after a standardized breakfast. Normal-weight female RE und URE performed a stop-signal task (SST) with food and non-food stimuli during sham or anodal tDCS. Food craving, hunger, and satiety were self-reported before and after tDCS. We employed a mixed between-subjects (group: RE vs. URE) and within-subjects factorial design (tDCS: anodal tDCS vs. sham; stimuli: food vs. control pictures). Results: Breakfast consumption was comparable for RE and URE, as well as craving, hunger, and thirst. Regarding inhibitory control, a significant two-way interaction between group and tDCS ermerged: RE had longer stop-signal reaction times (SSRTs) during sham tDCS, but they improved to the level of URE by application of anodal tDCS. Discussion: Results replicated an inhibitory control deficit in RE with longer SSRTs compared to URE without stimulation. During anodal tDCS to the rIFG, reduced SSRTs in RE indicated an improvement in inhibitory control. The findings suggest a specificity of rIFG stimulation in at-risk groups with regards to inhibitory control irrespective of craving.